The failure of Islamic education in promoting tolerance: a case study in Senior High School - Nuroniyah, Thoyibatun; Surahman, Cucu; Ragamustari, Safendrri Komara (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract. This study seeks to explain the important factors that cause the ineffectiveness of religious education in carrying out its function as a tool to promote the value of religious tolerance. This research is a case study at one of the State Senior High Schools in Bogor City. Policy analysis was carried out on three fundamental aspects, namely religious education policy analysis, curriculum and textbook analysis, and analysis of teachers’ perceptions of religious tolerance. The results of the study show that the discrepancy between the goals of religious education policies and the high potential for intolerance among students is driven by three things, namely; 1). Islamic education policies inacted indirectly encourage the application of the mono-religious education model, 2). the existence of teaching materials that contain elements of judgment against certain religious groups, 3). the teacher’s understanding of religious tolerance stops at the level of passive tolerance.Keywords: Islamic Education Policy, Islamic Religious Education, Religious Tolerance